2016
DOI: 10.21608/ejp.2016.90093
|View full text |Cite
|
Sign up to set email alerts
|

Use of Beneficial Microorganisms to Minimize the Recommended Rates of Macronutrients to Control Cucumber Damping off

Abstract: hizoctonia solani is a major problem causing damping-off of seedlings and root rot in mature plants and thus reducing nutrient uptake and plant stand. The aim of this study is to evaluate the effect of some bioagents in combination with the lowest doses of macronutrients on management of R. solani in cucumber plants. Four cucumber hybrids, i.e. hybrid 6, hybrid 9, hybrid 14 and Beit-Alpha F1 were tested for their susceptibility to the pathogenic fungi. Data indicated that Beit-Alpha, was highly susceptible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The highest increase was recorded for their mixed application where the increase percentage in POX activity was 80.4% and 87.3 % for P. carotovorum and B. cepacia treatments respectively, and the increase percentage in PPO activity was 37.1 % and 49.4 % for P. carotovorum and B. cepacia treatments respectively. The results are in agreement with Yousef et al (2016); Badr and El-Sharkawy (2018) and El-Sharkawy et al (2018 a,b) who reported that the application of Streptomyces increase the activity PPO and POX enzymes. POX enzyme stimulates the interaction of Ca 2+ signals required for inducing defence responses, phenols oxidation to quinine which are toxic to phytopathogens and taking part in cell wall polysaccharide processes like host plant cells lignification, suberization, and through the defence reaction against phytopathogens (Fayzalla et al, 2009;Hilal et al, 2016 andShafie et al, 2016).…”
Section: Effect Of Bcas On the Antioxidant Enzymes Activities In Onion Infected With Bacterial Rot Pathogenssupporting
confidence: 91%
“…The highest increase was recorded for their mixed application where the increase percentage in POX activity was 80.4% and 87.3 % for P. carotovorum and B. cepacia treatments respectively, and the increase percentage in PPO activity was 37.1 % and 49.4 % for P. carotovorum and B. cepacia treatments respectively. The results are in agreement with Yousef et al (2016); Badr and El-Sharkawy (2018) and El-Sharkawy et al (2018 a,b) who reported that the application of Streptomyces increase the activity PPO and POX enzymes. POX enzyme stimulates the interaction of Ca 2+ signals required for inducing defence responses, phenols oxidation to quinine which are toxic to phytopathogens and taking part in cell wall polysaccharide processes like host plant cells lignification, suberization, and through the defence reaction against phytopathogens (Fayzalla et al, 2009;Hilal et al, 2016 andShafie et al, 2016).…”
Section: Effect Of Bcas On the Antioxidant Enzymes Activities In Onion Infected With Bacterial Rot Pathogenssupporting
confidence: 91%
“…Defense-related enzymes such as POX, PPO and TAL regulate the production of soluble phenolics. The results are in concord with those of El-Sharkawy (2010); Yousef et al, (2016) and El-Sharkawy et al, (2018a,b) who reported that the application of AM fungi and Streptomyces induced the accumulation of phenolics and biosynthesis of lignin in plant cell walls. Values of each column followed by the same letter are not significantly different according to Duncans multiple range test (P ≤ 0.05).…”
Section: Effect Of S Coelicolor and Amf On The Total Phenols Contentsupporting
confidence: 88%
“…These results are in harmony with findings by (Adss et al 2017), who found that treatment of tomato fruits by elicitors after harvesting increased the activity of the PAL, PPO, and POD enzymes. The mechanisms of defense include earlier physical and chemical barriers that inhibit the pathogen (Hilal et al 2016;Shafie et al 2016;Yousef et al 2016;Farouk et al 2017;El-Sharkawy et al 2018;El-Sharkawy et al 2022).…”
Section: Enzymes Activities and Total Phenolsmentioning
confidence: 99%